Personalizing Heart Failure Care to the Patient With Cancer - Lambrinou, Ekaterini; Decourcey, Julia; Hill, Loreena Michelle (My University, 2022)
Purpose of Review: The current review describes the role of the cardio-oncology nurse and the need for personalized heart failure care for the patient with cancer. Recent Findings: It is a new role whereby cardiology or heart failure nurses care for patients with cancer who develop cardiotoxicity or cardiovascular diseases, either during the cancer therapy or in a later stage. Inter-disciplinary approach is important for individualized early treatment, shortened interruptions to cancer therapy, and irreversible cardiovascular injury prevention. Nurses have a key role in early evaluation and quality control of the care provided. Summary: This is a quite new clinical area and not much evidence exists for the development of clinical guidelines and pathways to support clinicians. More trials are needed for the development of clinical recommendations.
Keywords: Cardio-oncology nurse; Cardiovascular diseases (CVD); Anthracyclines; Cardiotoxicity; Razoxane